Cytokines in infection - Pang, T. (Malaysian Medical Association, 1993)
Cytokines are central to the development of effective immunity against microbial pathogens and their beneficial effects in the control of a variety of infections of man and animals are well-documented. However, it appears that cytokines may also have detrimental effects in infections by actually enhancing microbial growth. These observations emphasise the fact that many successful pathogens possess mechanisms enabling them to evade the immune response and that caution needs to be exercised in using cytokines as therapeutic agents to control infections in various human diseases.